2015
DOI: 10.4103/0976-237x.149295
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of early childhood caries among preschool children in Trivandrum and its association with various risk factors

Abstract: Background:Early childhood caries (ECC) is a severe form of dental decay with multi-factorial origin.Objectives:The aim of this cross-sectional study was to determine the prevalence and related risk factors of ECC among preschool children residing in rural and urban areas of Trivandrum district in Kerala.Methods:A sample size of 1329 preschool children of <60 months of age was randomly selected from rural and urban areas of Trivandrum and decayed missing filled teeth indices were recorded. A standardized quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
1
20

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 12 publications
3
31
1
20
Order By: Relevance
“…In both cases, there was an association between caries and the mother's educational level, nutritional status, child age, and presence of clinically visible plaque. The same associations were identified by others researches in different countries [12,14].…”
Section: Discussionsupporting
confidence: 52%
“…In both cases, there was an association between caries and the mother's educational level, nutritional status, child age, and presence of clinically visible plaque. The same associations were identified by others researches in different countries [12,14].…”
Section: Discussionsupporting
confidence: 52%
“…3,4 The factors responsible for ECC are the presence of dental plaque, susceptible host, fermentable carbohydrate diet, a high number of cariogenic microorganisms and time factor. 4,5 Early childhood caries is a common disease affecting very young children in today's era. In preschoolers, the prevalence of ECC ranges from 1 to 12% in developed countries and among high-risk group ranges from 50 to 80%.…”
mentioning
confidence: 99%
“…4 Most studies in indexed literature have focused on the prevalence of ECC in their target populations. [7][8][9][10][11][12] Results from these studies have reported a worrying prevalence rate of ECC (up to ~50%). [7][8][9][10][11][12] However, there is a dearth of studies assessing the incidence rates of ECC.…”
Section: Introductionmentioning
confidence: 99%